Nasrul Abit: Dari Seorang Birokrat Ke Dunia Politik Tahun 2000-2015 - Bellian Putri Mania; hendra Naldi (Jurusan Sejarah FIS UNP, 2022)
Abstract This study examines the biography of one West Sumatran figure, Nasrul Abit. Nasrul Abit is one of the political figures of West Sumatra, he started his political career from a reliable bureaucrat who has many achievements. The purpose of this research is the first, to explain the career journey of Nasrul Abit as a Civil Servant. Second, explain the turning point of Nasrul Abit's journey from being a civil servant to entering politics and his role. Third, explain the role and changes made by Nasrul Abit in the political field. The method used in this research is the historical method, the historical method consists of several stages, namely heuristics, source criticism, interpretation and histiography. The results of this study indicate that Nasrul Abit in his childhood was only a person who was born from such a simple family. Born to a simple family did not dampen his intention to pursue education. After completing his vocational education, Nasrul Abit went abroad to follow his uncle in Lampung, in Lampung he worked as a bureaucrat in the health department, while as a bureaucrat Nasrul Abit received many awards. In addition, he is also an active organizer in the Pesisir Selatan Family Association (IKPS). Being a reliable bureaucrat and active in the organization brought Nasrul Abit to enter the political realm and become the 2nd term Regent of Pesisir Selatan. Keywords: Biography, Bureaucrat, Politics